Attached to the World On the Anchoring and Strategy of Dutch Foreign Policy - Raad voor het Regeringsbeleid, Wetenschappelijke (WRR Rapporten, 2011)
Also available in Dutch "http://www.aup.nl/do.php?a=show_visitor_book&isbn=9789089643018">Aan het buitenland gehecht Few other countries are so interrelated with the world around us in political, economic, and social respects as the Netherlands. This means that the Dutch government needs to be alert in its response to the risks and opportunities presented by a rapidly changing world. Addressing this issue, the Scientific Council for Government Policy (wrr) offers some reflections in this report, guided by the question how the Netherlands can develop a foreign policy strategy that matches the changing power relations in the world and the radically changed character of international relations. The answer to this question is a reorientation. This means making transparent choices, making smarter use of Europe as our dominant arena, and, finally, choosing an approach that makes better use of the growing role of non-state actors. The report's recommendations not only underline the necessity of reorientation but also show how this could be accomplished in practice. This title is available in the OAPEN Library - http://www.oapen.org.